2017
DOI: 10.1155/2017/8196172
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Cockle Shell-Based Calcium Carbonate Aragonite Polymorph Nanoparticles with Surface Functionalization

Abstract: The development of cockle shell-based calcium carbonate aragonite polymorph nanoparticle synthesis method using the technique of mechanical stirring in the presence of dodecyl dimethyl betaine (BS-12) incorporated with surface functionalization demonstrated high homogeneity of sample product with good nanoparticles dispersion. The cockle shell-based calcium carbonate aragonite nanoparticle with functionalized surface was characterized using transmission electron microscopy (TEM), field emission scanning electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…The FTIR spectra of the composite P1, P2, and P3 materials in the 3500–700 cm −1 domain (Figure ) reveal the presence of bands characteristic to PVC (2950 cm −1 related to CH stretching from CHCl group, 2948 cm −1 from CH 2 groups, as well as several alkyls stretching modes and overtones in the 1500–800 cm −1 domain) and amorphous calcium carbonate (the 1360 cm −1 band, ascribed to asymmetric stretching of CO from the CO32 anion, which overlaps the CH and CCl rocking vibration bands of PVC . Due to overlapping of major IR absorption bands, the presence of wood phase could not be detected from the ATR–FTIR spectra.…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR spectra of the composite P1, P2, and P3 materials in the 3500–700 cm −1 domain (Figure ) reveal the presence of bands characteristic to PVC (2950 cm −1 related to CH stretching from CHCl group, 2948 cm −1 from CH 2 groups, as well as several alkyls stretching modes and overtones in the 1500–800 cm −1 domain) and amorphous calcium carbonate (the 1360 cm −1 band, ascribed to asymmetric stretching of CO from the CO32 anion, which overlaps the CH and CCl rocking vibration bands of PVC . Due to overlapping of major IR absorption bands, the presence of wood phase could not be detected from the ATR–FTIR spectra.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the biological safety evaluation of porous CSCaCO 3 NP on hFOB 1.19 cells showed that CSCaCO 3 NP could be a promising drug nanocarrier with wide safety level [16,25]. Danmaigoro et al [17] and Ghafar et al [106] claimed that CaCO 3 NP of biogenic cockle shell origin have relatively large loading content capacity, encapsulation efficiency, functional group endings for electrostatic ion bonds (hydroxyl and carboxylic groups), surface structural porosity, higher surface area and response to pH degradation which explains its uniqueness as a novel inorganic compound for nanocarrier application. It was reported to exhibit great promising potential as a drug nanocarrier, these have become possible due to its immense biomedical utilizations attributable to its biocompatibility, osteoconductivity, pH sensitivity, hydrophilic nature as well as slow biodegradability [9].…”
Section: Cockle Shell (Anadara Granosa)mentioning
confidence: 99%
“…The increase in the use of nanoparticles for biomedical applications encourages the continuous synthesis and development of the aragonite polymorphic form cockle shell-derived calcium carbonate nanoparticle (CSCaCO 3 NP) of biogenic origin for a targeted drug delivery system [17]. This marine species product is known to possess good quality and pure crystalline CaCO 3 in purely aragonite polymorph form [77,78] more so, heavy metals such as arsenic, lead or mercury are absent in the shells [12,106,107].…”
Section: Cockle Shell (Anadara Granosa)mentioning
confidence: 99%
See 1 more Smart Citation
“…Powderizing CaCO3 can be a solution and this has been done by a bottom-up approach such as the precipitation reaction occurring by mixing Ca 2+ and CO3 2ions or a top-down approach such as the pulverization of cockle shell. 61 Rangari and co-workers loaded the model drug, 5-fluorouracil into eggshell-derived CaCO3 nanoparticles, 62 and prepared tablets consisting of the CaCO3 nanoparticles (more than 80 wt%) and binders. New Zealand White Rabbits were used as an animal model for digestion and radiographs were taken after ingesting the tablets.…”
Section: Caco 3 Particles As Therapeutics and Therapeutic Carriersmentioning
confidence: 99%